Adaptive Graphical User Interface for Web Applications Using Aspect Oriented Component Engineering - Zaman, Atif; Ahmad, Mudassar; Ahamd, Shafique; Mustafa, Tasleem (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Graphical User Interface (GUI) is considered to be an essential part in any web applications development. Aspect-Oriented Component Engineering (AOCE) is new approach for developing more and higher quality reusable and adaptable software or web applications components. AOCE uses the idea of providing and requiring services. Adaptable user interface for AOCE based development has not yet been considered to web applications. Simple and easy user interface facilitate users by which application or web interface can be operated effectively. The purpose of this study is to discuss popular user interfaces and suggestions for adaptable GUI designing. The example of adaptation at different levels includes architecture, presentation, extension and composition. Furthermore the AOCE common systemic aspects are discussed for web interfaces adaptivity.